Optimizing foreign exchange reserves: Protection against external shocks in Ghana - Abdul-Rahaman, Abdul-Rashid; Hongxing, Yao; Alhassan Alolo Akeji, Abdul-Rasheed; Ayamba, Emmanuel Caesar; Bernard Pea-Assounga, Jean Baptiste; Alhassan, Mohammed Kamil (Frontiers in Psychology, 2022)
Using Least Square Residual Minimization techniques, this paper develops a reserve model that optimizes the cost of holding reserves and also assists in fixing optimal reserve levels that double as better predictors of economic trends. This paper concludes that the developed reserve model in this research is better positioned to eliminate the procyclicality and perverse rush in reserve build-ups experienced in developing and emerging countries by effectively setting the reserve stock against economic trends. Wrapping up, the research fixes a benchmark of 0.7 –to 1.2 of the previous year's optimal value as the optimal reserves. This benchmark is only appropriate when the past optimal value is known. However, in the absence of this knowledge, a benchmark between 2 to 6 times of the average inflows in an economy is recommended for short-term analysis or analysis with small data observations. However, for long-term analysis or analysis with large data frequency (i.e. exceeding 13 data observations), the reserve stock should be fixed on a benchmark of 2 to 9 times of the average inflows. Quote: "Reserve models produce imprecise estimates of reserve stocks" (IMF article IV consultative report, 2017).